Development of Test Rig for Centrifugal Air Strainer - N, Karthick; N, Gayathri; T V B, Babu; S, Nandhakumar; S, Mugunthan; B, Yuvaraj (International Journal of Engineering and Technology, 2018)
This paper is a description of an alternative method for the testing of air strainer in the railways. In traditional method they can’t test the filter with full accuracy, so semi-automatic method is needed to check the sealing of the filter effectively. Test rig is used to check the sealing of the air strainer. This paper addresses two major issues from the previous method of testing.(1)     Requirement of skilled labors in work.(2)     Precise inspection is   not possible. The test rig being used currently requires more setting up time and the cost of the process is more. This paper describes a test rig which can reduce cost of the process and be able to reduce the human error by semi-automatic method.